SEASONAL AVERAGE FLOW IN RÂUL NEGRU HYDROGRAPHIC BASIN - VIGH MELINDA (Aerul şi Apa: Componente ale Mediului, 2015)
The Râul Negru hydrographic basin is a well individualised physical-geographical unit inside the Braşov Depression. The flow is controlled by six hydrometric stations placed on the main river and on two important tributaries. The data base for seasonal flow analysis contains the discharges from 1950-2012. The results of data analysis show that there significant space-time differences between multiannual seasonal averages. Some interesting conclusions can be obtained by comparing abundant and scarce periods. Flow analysis was made using seasonal charts Q = f(T). The similarities come from the basin’s relative homogeneity, and the differences from flow’s evolution and trend. Flow variation is analysed using variation coefficient. In some cases appear significant Cv values differences. Also, Cv values trends are analysed according to basins’ average altitude.